Mixed Diets Reduce the Oxidative Stress of Common Carp (Cyprinus carpio): Based on MicroRNA Sequencing - Yang, Song; Luo, Jie; Long, Yalan; Du, Jie; Xu, GangChun; Zhao, Liulan; Du, Zongjun; Luo, Wei; Wang, Yan; He, Zhi (Frontiers in Physiology, 2019)
The rice-fish mode, a mode of ecological aquaculture, has become a popular research topic in recent years. The antioxidant capacity of fish can be affected by the type of diet. Three groups of adult common carp (initial weight 517.8 ± 50 g) were fed earthworm (group A), earthworm + duckweed (group M) and duckweed (group P). The antioxidant capacity of common carp (Cyprinus carpio) was evaluated by histopathological sectioning, antioxidant enzyme activity and the miRNA transcriptome profile. The pathological changes in group M were lighter than those in group C and group A. The activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) significantly increased in group M, and the malondialdehyde content (MDA) significantly decreased (P < 0.05). Additionally, nine differentially expressed miRNAs (DEMs) were found between group A and group M, and eight DEMs found between group P and group M were identified in the liver of common carp. Five miRNAs were reported to be related to oxidative stress, including miR-137-3p, miR-143-3p, miR-146a-5p, miR-21-5p and miR-125b-5p. Compared with group M, all five detected miRNAs were upregulated in group A and four of the detected miRNAs were upregulated in group P. The targets of the five miRNAs were further predicted via functional analysis. Our study confirmed that omnivorous common carp exhibit stronger antioxidant capacity when feeding on both an animal diet and plant diet.